Kant's doctrine of transcendental illusion - Grier, Michelle, 1960- (Modern European philosophy., 2001)
This major study of Kant provides a detailed examination of the doctrine of transcendental illusion in his theoretical philosophy. The author argues that we cannot understand Kant unless we take seriously his claim that the mind inevitably acts in accordance with ideas and principles that are 'illusory'.